Efficacy of natural prodicts to control Callosobruchus maculatus (Fab.) in stored cowpea (Vigna unguiculata (L.) Walp). - Azevedo, Francisco (2008)
In search of alternative to substitute chemical products in the control Callosobruchus maculatus in stored cowpea, natural products such as Pironat® (extrato pirolenhoso), Rotenat® (rotenona), Natuneem® (azadiractina), Bovenat® (Beauveria bassiana), and Metanat® (Metarhizium anisopliae), plus a control sample have been evaluated. Each treatment was replicated four times and each replication consisted of 50 grains stored in 300mL transparent acrylic cups covered by white cloth. Products were applied once prior the infestation. Evaluations were carried out regarding mortality, oviposition and adult emergence, respectively, seven and twenty-seven days after applying the products. The Rotenat® was the most efficient product for controlling bean weevil. Metanat® was most efficient for oviposition control. The Natuneem® exhibited low efficacy due to the low concentration used to treat the grains of cowpea. Although none of the products reached 100% control, they may be applied in programs of Integrated Management of Callosobruchus maculatus for costing low, for being of easy application, and for not causing any environmental impact in terms of risk of toxic residues in grains.